THE ESSENCE AND MECHANISMS OF INVESTMENT IN RESIDENTIAL REAL ESTATE - KAPUSTYNSKYI, Ruslan (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The author describes in the article that the deterioration of the economic situation in Ukraine due to hostilities causes the need for careful analysis, planning and finding ways to attract investments in the field of residential real estate. The destruction of a large part of the housing stock, a significant volume of internal migration of the population due to the loss of housing in the territories primarily close to active hostilities, acutely raises the issue of analyzing and improving the existing mechanisms of investing in residential real estate in order to find new investors in the middle of the country and from abroad. The author considered the essence and features of investing in residential real estate in Ukraine. The current legal documents regulating the sphere of infestations in residential real estate are considered and the main sources of investments are given in accordance with the current legislation. The main goals of investors and the main subjects of the residential real estate market have been determined. It is emphasized that a significant share of investments in residential real estate is occupied by institutional investors. The classification of the main forms of investment in real estate according to the principle of building capital (on the basis of equity, loan and mixed capital) is presented. The main financing mechanisms for residential real estate objects have been identified: construction financing funds, issuance of targeted bonds, real estate transaction funds, joint investment institutes; their features are investigated, the main advantages and disadvantages are highlighted in relation to the financial security of the investor and from the side of the regulator - the state. Considered a fairly popular nowadays, but not regulated by law, method of investing in real estate - an investment contract with a developer; its risks are emphasized. It is noted that the risk of loss of real estate or invested own monetary assets always remains with the investor, regardless of the type of investment mechanism.